Preserving songket through sustainable packaging design - Ziratul Aqma Norzaman, Nor (International Journal of Engineering and Technology, 2018)
To date, we have never come across any significant study conducted on the Songket packaging design. Most available research findings focus on the motifs and how it is applicable to the contemporary world. Songket packaging design has not evolved parallel to the rapid growth of Songket textile design. From the observation done, today, most of the Songket especially sampin packaging design relies on conventional packaging and other reliable for preserving its quality in long term storage. This research aim to test out the applicability design special for storing sampin.Â Â